Analisis Konstruksi Verba Pasif pada Halaman Judul Surat Kabar - Wurjantoro, Wawan (Journal of Comprehensive Science, 2025)
The research on passive verb construction in national newspaper headlines aims to identify passive construction markers and Indonesian sentence patterns found in newspaper headlines, by checking the presence or absence of complementary objects. This research is a research using a qualitative descriptive method. In this study, the researcher did not use a measuring tool in the form of numbers in testing or analyzing data. The findings suggest that the passive form is tested by converting it back into an active sentence structure. This process involves promoting the passive sentence complement object to the active sentence subject, while lowering the passive sentence subject to the active sentence object. Furthermore, passive formation occurs when active verbs are transitive. Not all verbs in the passive construction are transitive verbs.